Bio-efficacy of different casing materials and changes in their physico-chemical properties during cultivation of A. bisporus - Sharma, Shubham; Gupta, Dharmesh; Thakur, Manisha (Mushroom Research, 2020)
Different casing materials consisted of Â FYM + Soil(1:1v/v) , Spent compost + 8% calcium chloride, F YM + Spent compost + Soil (2:1:1), Coir pith + FYM+ soil (l:1:1), Coir pith + Soil (1:1), Spawned casing, Burnt rice husk (20%) +FYM (40%) +Soil (40%) and Vermicompost casing. Maximum sporophore (1695.67) per 100 Kg compost were obtained by spawned casing followed by control treatment having casing mixture of FYM + soil (1:1 v/v) i.e. 1573.33 sporophores.